1982
DOI: 10.1007/bf00337963
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analysis of in vivo recombinants between bacteriophage λ DNA and pBR322

Abstract: The nucleotide sequences involved in the illegitimate recombination of four recombinants between bacteriophage lambda DNA and pBR322 in E. coli (lambda TA6, lambda KA3, lambda TA1R, and lambda KA7) were determined. Each resulted from recombination between regions of homology of 10 to 13 base pairs. The presence of a recA+ allele was found to stimulate recombination between lambda DNA and pBR322 approximately 10-fold. Lambda TA6, lambda KA3, and lambda KA7 were isolated in the presence of a recA+ allele and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Therefore, they suggested that the recombinations result from an exchange of DNA gyrase subunits bound to different sites. The nucleotide sequences at the A-plasmid junctions of one of these recombinants were determined and the results were consistent with this model (5).We have isolated several A-pBR322 recombinants that were generated in recA+ and recA-derivatives of E. coli (6,9). The sequences at the A-pBR322 junctions of four of these recombinants were determined (6).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, they suggested that the recombinations result from an exchange of DNA gyrase subunits bound to different sites. The nucleotide sequences at the A-plasmid junctions of one of these recombinants were determined and the results were consistent with this model (5).We have isolated several A-pBR322 recombinants that were generated in recA+ and recA-derivatives of E. coli (6,9). The sequences at the A-pBR322 junctions of four of these recombinants were determined (6).…”
mentioning
confidence: 61%
“…Another possible explanation for some illegitimate recombination events is that they are generated by DNA gyrase (4)(5)(6). Ikeda et aL (4,5) discovered that illegitimate recombinations between A DNA and plasmid pBR322 occur in extracts of E. coli and that the frequency of recombination is increased by the addition of oxolinic acid (4,5), which is an inhibitor of DNA gyrase (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The integration products of pE194 recombination show similarity to the products of other illegitimate recombinations, such as the recA-independent cointegrate fusions between pBR322 and the F-factor oriVI region (33) and also lambda-pBR322 recombination (24,27). These recombination events occur at low frequency (10-8 to 10-9) in E. coli recA mutants, and the recombination products appear to rise from reciprocal recombination between sequence identities of 10 to 13 bp (24,33).…”
Section: Discussionmentioning
confidence: 88%
“…These recombination events occur at low frequency (10-8 to 10-9) in E. coli recA mutants, and the recombination products appear to rise from reciprocal recombination between sequence identities of 10 to 13 bp (24,33). Most models for producing illegitimate recombination events of this type involve errors in DNA metabolism at first proposed by Franklin (10).…”
Section: Discussionmentioning
confidence: 99%